2014
DOI: 10.1007/s11906-014-0511-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual Renin-Angiotensin-Aldosterone Blockade: Promises and Pitfalls

Abstract: Single renin-angiotensin-aldosterone system (RAAS) blockade has been shown to be effective and safe for the treatment of hypertension, coronary heart disease (CHD), heart failure (HF), diabetes, and chronic kidney disease (CKD) with proteinuria. Due to the action of RAAS blockers at various levels of the RAAS cascade, it was hypothesized that dual RAAS blockade would result in more complete inhibition of angiotensin II (Ang II) production and be more effective in blocking its detrimental cardiovascular remodel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Unfortunately, several clinical trials (ONTARGET, ALTITUDE and VA NEPHRON-D) in patients with hypertension, heart failure, and chronic kidney disease with proteinuria have demonstrated no beneficial effects of dual versus single RAAS blockade, but a higher incidence of adverse events. 130 Some new combined agents affecting RAAS occurred recently. According to the latest network meta-analysis of Xie et al., ARNI, a novel dual-acting angiotensin receptor-neprilysin inhibitor has the highest probability of being the most effective therapy for heart failure and reduced ejection fraction compared to ACE-Is and/or ARBs.…”
Section: Combined Treatment—another Approach To Raas Blockingmentioning
confidence: 99%
“…Unfortunately, several clinical trials (ONTARGET, ALTITUDE and VA NEPHRON-D) in patients with hypertension, heart failure, and chronic kidney disease with proteinuria have demonstrated no beneficial effects of dual versus single RAAS blockade, but a higher incidence of adverse events. 130 Some new combined agents affecting RAAS occurred recently. According to the latest network meta-analysis of Xie et al., ARNI, a novel dual-acting angiotensin receptor-neprilysin inhibitor has the highest probability of being the most effective therapy for heart failure and reduced ejection fraction compared to ACE-Is and/or ARBs.…”
Section: Combined Treatment—another Approach To Raas Blockingmentioning
confidence: 99%
“…Based on the current evidence, many investigators no longer recommend the routine use of dual RAAS blockade for the treatment of hypertension or chronic kidney disease, except for the presence of HF with reduced EF or DN with proteinuria [8].…”
Section: Discussionmentioning
confidence: 99%
“…The latest research demonstrates that the long-held belief that a more complete blockade of RAAS, with a combination of two of the three existing RAAS blockers (ACE inhibitors (ACEi), ARBs, or DRIs), has come under serious doubt regarding its effectiveness and safety for the treatment of patients with hypertension, or nephropathy with proteinuria [8]. With regards to clinical studies, it was concluded that, in human diseases, there are currently no proven benefits of the combined ACEi and ARB over single drug RAAS blockade.…”
Section: Contrasting Evidence On the Dual Raas Blockadementioning
confidence: 99%
“…Recently Chrysant and Chrysant (2015), based on the evidences available suggested that dual RAS blockade should not be a routine treatment for cardiovascular disorders, but included as reasonable indications for dual-blocking diabetic nephropathy with proteinuria and heart failure with reduced ejection fraction.…”
Section: Combination Therapy In Ckdmentioning
confidence: 99%